KREATIVITAS SD TA’MIRUL ISLAM SURAKARTA DALAM PELATIHAN TARI - Hartanto Hartanto (Institut Seni Indonesia Surakarta, 2020)
This article discusses creativity Elementary School Ta’mirul Islamic Surakarta in dance training. The goal of the training is grade 3.4, 5 and 6. The form of training is traditional dance creations and creativity in dance collaboration with the music of rabbana (Hadrah). Results of the training on traditional dance creations is the dance Soyong and dance Pangpung, while creativity produces motion of the song with the music of tambourines to MAPSI race. In the race, get the first winner District and Municipal level, and advance to the provincial level. This training is not to produce a perfect performance shape or focus on the mastery of the material as well, but it is more emphasized on the process, in case of emphasizing student involvement in tapping the creativity of the student’s ability with freedom and flexibility in managing the body and expresses it to be a show. This is supposed to give an understanding of basic creativity, to form a creative media, to perform the creative works and to document audio visual in order to be used as a reference in dance studying in elementary school.Keywords: creativity, dance, student of Elementary School, training.